2010
DOI: 10.1007/s10529-010-0309-6
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of zirconium phosphate by a Serratia sp.: a benign system for the removal of radionuclides from aqueous flows

Abstract: Metal phosphate deposited enzymatically on Serratia sp. has been used successfully for the removal of radionuclides from aqueous flows. Previous studies using biogenic hydrogen uranyl phosphate (HUP) on Serratia sp. biofilm showed removal of 100% of (90)Sr, (137)Cs, and (60)Co via their intercalation into biogenic HUP crystals. Zirconium phosphates (ZrP) offer a potential non-toxic and non-radioactive alternative to HUP for water decontamination. A method was developed for biomanufacturing ZrP. Biogenic ZrP re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Another approach is to use a sorbent or ion exchange material that can be disposed of once its full capacity is reached. Traditional ion exchangers such as titanates and hexacyanoferrate are standard in the nuclear industry but these can be rather specific for particular target metals (IAEA 2002), whereas recentlydescribed biogenic phosphate mineral matrices based on uranyl hydrogen phosphate (HUP; PatersonBeedle and Macaskie 2006) and zirconium phosphate (Zr-P; Mennan et al 2010) take up a range of metals and have the potential to operate under a wide range of pH values, with a potential capacity several orders of magnitude larger than traditional materials (Mennan et al 2010). Furthermore, growth of this biomass is rapid and cheap (several kg fresh weight after 24 h in batch growth at 30°C; Macaskie et al 1995); biogenic material does not require procurement of materials (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is to use a sorbent or ion exchange material that can be disposed of once its full capacity is reached. Traditional ion exchangers such as titanates and hexacyanoferrate are standard in the nuclear industry but these can be rather specific for particular target metals (IAEA 2002), whereas recentlydescribed biogenic phosphate mineral matrices based on uranyl hydrogen phosphate (HUP; PatersonBeedle and Macaskie 2006) and zirconium phosphate (Zr-P; Mennan et al 2010) take up a range of metals and have the potential to operate under a wide range of pH values, with a potential capacity several orders of magnitude larger than traditional materials (Mennan et al 2010). Furthermore, growth of this biomass is rapid and cheap (several kg fresh weight after 24 h in batch growth at 30°C; Macaskie et al 1995); biogenic material does not require procurement of materials (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For convenience the column tests used high background concentrations of ‘cold’ surrogates (0.33 mM) and hence column saturation occurred relatively quickly; at realistic radionuclide concentrations the capacity and hence durability of this approach would exceed that of commercial ion exchange materials (c.f. Mennan et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Application of this technique to wastes which already contain uranium would present no problem since this would overcome the need for addition of UO 22+. For potable water treatment a non‐toxic biogenic “host” metal phosphate, for example, zirconium phosphate (Mennan et al, 2010) would be mandatory. Preliminary tests (M. Paterson‐Beedle, unpublished data) have shown this potential but here the advantage of uranium as a “local” radiation shield would be lost.…”
Section: Resultsmentioning
confidence: 99%
“…For clean‐up of water supplies, a toxic uranium‐based material is unacceptable. Recent work has shown that biogenic zirconium phosphate has potential as a nontoxic biogenic ion exchanger for fission products (Mennan et al ., 2007).…”
Section: Non‐redox Systems For the Formation Of Biomineralsmentioning
confidence: 99%